Pengaruh Asimetri Informasi Dan Komitmen Organisasi Terhadap Kecenderungan Kecurangan Akuntansi Pada Pengelolaan Badan Usaha Milik Desa (BUMDes) Simpan Pinjam Di Kabupaten Bangli - Ni Made Aryaningsih; Ni Komang Sumadi (UNHI Press, 2022)
Business entities whose sources of capital come from villages are often referred to as BUMDes (Village Owned Enterprises). BUMDes was established to manage all village assets for the welfare of the community. The importance of the role of BUMDes for villages is no wonder its existence needs to be protected from fraudulent efforts. This research was conducted to look at the factors that cause fraud where the factors to be studied are Information Asymmetry and Organizational Commitment. 170 employees of BUMDes Savings and Loans in Bangli Regency were used as a population of which 118 people were used as samples. This study uses multiple linear regression analysis techniques and produces data where asymmetric information has a unidirectional (positive) relationship to the tendency of cheating. Organizational commitment from this study shows a negative relationship with the tendency of fraud.